SUPPLIER STRUCTURE AND PERFORMANCE EVALUATION OF SUPPLIER NETWORK PHASE RICE SUPPLY CHAIN MANAGEMENT IN SOUTH SUMATRA - bidarti, agustina; Hadi Darwanto, Dwidjono; Hartono, Slamet; Jamhari, Jamhari (AGRARIS: Journal of Agribusiness and Rural Development Research, 2019)
This study aims to identify the mapping, measure performance, and analyze problems in the structure of rice supply chain management on the supplier network phase in South Sumatra. Afterward, the result of this study is used as the basic consideration to improve the rice supply chain performance on indicators that have problems. Data collection was conducted by direct interview, questionnaire, and observation. This study used descriptive qualitative and several analysis tools as the data such as Supply Chain Operation Reference Model (SCOR), Analytical Hierarchy Process (AHP), Objective Matrix (OMAX) and Traffic Light System (TLS). According to the rice supply chain mapping on supplier network phase, there are three rice supply chains. Based on the interview, the farmers’ main problem as the main producers of the rice supply chain in South Sumatra is the limitation of unhusked rice price information in harvesting in the financial flow of rice supply chain. Based on the weighting result by OMAX scoring system, the total index value is 7.28, or in the yellow category which means that the performance of LICM rice- industry company in South Sumatra has not achieved the expected performance in terms of rice supply chain even though the result is close to the pre-determined target.